THEMATIC INTERPRETATION TRAINING ON RELIGIOUS MODERATION FOR DAI (PREACHER) AND RELIGIOUS COUNSELORS - An, Andri Nirwana; Mahmudulhassan, Mahmudulhassan; Muthoifin, Muthoifin; Waston, Waston; Prakoso, Sajiwo Tri; Saputro, Yogi Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research explores the effectiveness of thematic Tafsir training in promoting religious moderation among Dai (preachers) and Religious Counselors in Indonesia. The training aimed to equip religious leaders with the necessary skills to interpret Quranic teachings on themes such as tolerance, inclusivity, and peace, with a focus on addressing contemporary issues of extremism and religious pluralism. Thematic Tafsir, which focuses on interpreting the Quran based on specific themes, was used to help participants contextualize religious teachings in the diverse and multicultural landscape of Indonesia. The training included theoretical and practical components, such as case studies, role-playing exercises, and reflection sessions. The results indicated that the training significantly enhanced the participants' understanding of religious moderation and improved their ability to communicate these values in their communities. The program’s success highlights the importance of providing Dai (Preacher) and Religious Counselors with professional development opportunities to strengthen their role in promoting peace, tolerance, and social harmony in Indonesian society.